Biodiversidade de borboletas frugívoras (Lepidoptera: nymphalidae) em diferentes ecossistemas - Fleck, Marciane Danniela (2014)
The process of fragmentation of native environments has been increasing gradually in recent decades and forming small forest remnants in place of continuous and preserved forest. These effects on natural resources may cause changes in diversity and composition of various groups of animals, including butterflies. Among several factors responsible for the occurrence and distribution of species of guild fruit-feeding butterflies, the heterogeneity and structural complexity of the environment may be crucial to their survival. Thus, the present study sought to expand the knowledge on the guild of fruit-feeding butterflies for Médio Alto Uruguay region in Rio Grande do Sul, since the studies conducted until this moment have not used the same collection procedure. This study is also relevant for the conservation of the Deciduous Seasonal Forest, already significantly altered by human action. The objectives of this study were divided into two chapters. Chapter I aimed (i) to determine the diversity and composition of the guild fruit-feeding butterflies in two fragments of secondary formation of the Deciduous Seasonal Forest in environments in the edge and forest interior, (ii) to evaluate the edge effect regarding richness, composition and abundance of guild fruit-feeding butterflies, and (iii) to verify the influence of microclimate variables of temperature, relative humidity, wind speed, and brightness. Chapter II aimed to (i) sample the guild of fruit-feeding butterflies in an area of pasture Cynodon sp., and (ii) determine the population dynamics of this guild with respect to medium temperature and relative humidity of air and the total pluviosity of the site. From August 2012 to July 2013, fortnightly collections were performed using traps with attractive bait, modified of the model "Van Someren-Rydon", consisting of fermented banana with sugar cane juice. Four attractive traps were placed in the fragments in the edges and four traps were installed inside, distant 40 m from the edge of the fragment, suspended in tree branches. In the area of grazing of Cynodon sp., four traps were placed suspended on wooden supports. All 20 traps were placed 1.70 m above the ground. 2,077 specimens of fruit-feeding butterflies from 46 species and 4 subfamilies were captured. In the fragments analyzed, 2,003 specimens of fruit-feeding butterflies were identified. No significant difference between the edge and the interior environments of the forest fragments was observed when the richness of fruit-feeding butterfly species was compared. Microclimate variables of temperature, relative humidity, wind speed and brightness are significantly related to the distribution of species of fruit-feeding butterflies when canonical correspondence analysis was used in the interior and edge of fragments, with 10 and 30 years without exploration, respectively. The species, Yphthimoides affinis (Butler, 1867) found in one of the fragments is a new record for our state, Rio Grande do Sul. In the area of pasture of Cynodon sp., 74 specimens of fruit-feeding butterflies from 16 species as well as the highest richness of species was found in summer and spring seasons showing the seasonal variation of this guild in the area.